A BIBLIOMETRIC ANALYSIS ON THE GREEN INVESTMENT - Muliani Muliani (STIE Pelita Nusantara Semarang, 2023)
Implementation green investment sustainable and responsible has become a priority for every company and investor because the more rising high alarm signal on environmental issues as well as for maximizing profits and harmonious development with the environment. Studies it focused on 3 research questions . Information was collected to examine the above research questions and a network map was applied. This study aims to check the publication of documents based on most influential articles, country co-authors, and appearances with green investment keywords. Key words categorized as into some cluster. The type of analysis used is bibliometric analysis . Study This retrieve the latest data A total of 701 articles from a scientific database that is SCOPUS of 2018- 2023 and network analysis use VOSviewer software. This study find that There are 2 most influential articles to green investment research with citation the most, the country that contributes the most in green investment research with amount article the most and the most frequent keywords used. This study has certain limitations and is concluded by providing implications and suggestions for future studies. The end this study will provide more insights to researchers, academics, and others to find research gaps in the field of green investment.